Market structure and competitive conditions in the Arab GCC banking system - Saeed al- Muharrami; Kent Matthews; Yusuf Khabari (Cardiff University, Cardiff Business School, 2006)
This paper investigates the market structure of Arab GCC banking industry during the years of 1993 to 2002 using the most frequently applied measures of concentration kbank concentration ratio (CRk) and Herfindahl-Hirschman Index (HHI) and evaluates the monopoly power of banks over the ten years period using the “H statistic” by Panzar and Rosse. The results show that Kuwait, Saudi Arabia and UAE have moderately concentrated markets and are moving to less concentrated positions. The measures of concentration also show that Qatar, Bahrain and Oman are highly concentrated markets. The Panzar-Rosse H-statistics suggest that banks in Kuwait, Saudi Arabia and the UAE operate under perfect competition; banks in Bahrain and Qatar operate under conditions of monopolistic competition; and we are unable to reject monopolistic competition for the banking market in Oman.
Keywords: G21; L1; D40; 330; GCC countries; Concentration; Market structure; Competition; Panzar-Rosse model; k-bank concentration ratio (CRk); Herfindahl-Hirschman Index (HHI); Bankensystem; Marktstruktur; Wettbewerb; Unternehmenskonzentration; Arabische Golf-Staaten